Proposal for Review and Reform of OSH Legislation for Construction Industry in Malaysia - Rozanah Ab. Rahman (New Ideas Concerning Science and Technology Vol. 9, 2021)
Construction sector is dynamic and it differs from other industries in terms of the hazards exposed to its workers. The activities carried out at the construction sites are very diverse and every construction phase posts different hazards. Thus, appropriate worksite’s hazard control is crucial and demand for an updated OSH legislation is long-awaited. A complete legal framework is warranted to cater for the alarming state of safety and health issues in the industry. The proposed unification of the Factories and Machinery Act 1967 and the Occupational Safety and Health Act 1994, with current and updated Regulations for construction activities shall become a strong move towards effective implementation of the legislation. Efforts shall be taken toward strengthening the OSHA 1994 and not to retain the enforcement of both the FMA and the OSHA, as what believed by the authority and the industry to be necessary many years ago. It is no longer appropriate for both legislations to exist and appropriate steps shall be taken to expedite the formulation of the Regulations and Approved Code of Practice under the OSHA 1994, particularly for construction activities, in order to clarify and explain the general safety duty laid down in the OSHA 1994.